A Correlation Between Students’ Self Confidence And Their Academic Achievement In Speaking Course Of The Third Semester At Lakidende University - M Fadli (Jurnal Pendidikan dan Konseling (JPDK), 2022)
This research is about A correlation between Students’ self confidence and their academic achievement in speaking course of the third semester at Lakidende University. The problem statement of this research was is there any significant correlation between students’ self confidence and their academic achievement in the speaking course. The objective of this research is to find out significant correlation between students’ self confidence and their academic achievement in the speaking course of the third semester at Lakidende University.The subject of this research was the students of the third semester at Lakidende University, there were 40 students of the third semester in Lakidende University academic year 2019/2020 that containing of one class. The saturated sample or total sampling that used in this research were 40 students which consisting of 9 males and 31 females. This research was a quantitative research that using a correlation design. The data was obtained from questionnaire of self confidence and academic achievement.This research was conducted systematically by taken score academic achievement and questionnaire for self confidence. After calculating the result of the students’ score in questionnaire self confidence and academic achievement, the researcher found that the students of Lakidende University had mean score of self confidence high with score 81.10 % and mean score of academic achievement was high with score 81.75 %. Furthermore, the coefficient correlation rxy = 0.705. It mean that, the correlation was high (there was correlation). Based on the data above, the researcher concludes that the H0was rejected and H1was accepted it means that there is correlation between students’ self confidence and their academic achievement in speaking course of the third semester in academic year 2019/2020 at Lakidende University.